2013
DOI: 10.2527/jas.2012-5914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forage species or concentrate finishing on animal performance, carcass and meat quality1,2

Abstract: Angus-cross steers (n = 128; initial BW = 270 ± 3.8 kg) were used in a 3-yr study to assess effects of forage species grazed before slaughter versus concentrate finishing on carcass and meat quality. At the completion of the stockering phase, steers were randomly allotted to mixed pasture (MP; n = 36/yr) or corn-silage concentrate (CON; n = 12/yr) finishing treatments. At 40 d before harvest, MP steers were randomly divided into 3 forage species treatments: alfalfa (AL), pearl millet (PM), or mixed pasture (MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
106
12
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 48 publications
22
106
12
7
Order By: Relevance
“…In our study beef PUFAs content was higher than the values reported by others (Scollan et al, 2006) LA is the primary PUFAs in both grass/forage-fed and grain-finished beef providing 60-85% of total PUFAs (Duckett et al, 2013). Usually the percentage of PUFAs in beef is increased by as much as 25% in response to grass-feeding due to the lower intramuscular total fat of most grass-fed beef.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In our study beef PUFAs content was higher than the values reported by others (Scollan et al, 2006) LA is the primary PUFAs in both grass/forage-fed and grain-finished beef providing 60-85% of total PUFAs (Duckett et al, 2013). Usually the percentage of PUFAs in beef is increased by as much as 25% in response to grass-feeding due to the lower intramuscular total fat of most grass-fed beef.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the total www.scholink.org/ojs/index.php/ra estimated amount of PUFAs in steaks from U.S. grass/forage-fed cattle may be up to 75mg lower per 100g of beef, primarily as LA (Daley et al, 2010). Only 16 to 26 mg ALA have been reported in various lean cuts for grass/forage cattle versus 4-13 mg ALA from U.S. grain-finished beef, whereas but only traces of n-3 LC-PUFAs are noted in meat from U.S. grass/forage-fed cattle (Duckett et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although biological type can certainly influence carcass fat deposition (Ito et al, 2012), the grainbased diet of HCF had a positive effect on flavor liking despite the Bos indicus influence of those cattle. Grass fed beef has been reported by U.S. consumers to have less acceptance for beef flavor due to off-flavors (Duckett et al, 2013). Despite previous evidence of a reduction of "grassy" off-flavor from including grain in the animal diet (Larick et al, 1987), in our study no differences in flavor liking scores were observed between HSC and HDP, whereas HCF was more liked than either.…”
Section: Consumer Flavor Likingcontrasting
confidence: 55%
“…However, differences in beef production systems, such as those in the U.S. compared to those in Central America, can affect flavor (Smith et al, 1985;Savell et al, 1987). Beef from animals raised on a finishing diet with grains tend to deposit more fat (Duckett et al, 2007;Duckett et al, 2013), positively affecting flavor (Umberger et al, 2000). The grain finishing diet of HCF may have been responsible for similar scores between HCF and U.S. treatments.…”
Section: Consumer Flavor Likingmentioning
confidence: 99%
“…REZENDE et al (2012) evaluating Holstein cattle slaughtered at 395 kg, also found no difference in eating plans in growing and finishing for the loin eye area, obtaining average values of 51.46cm². DUCKETT, et al, (2013), found superiority for all quantitative carcass traits who compared finishing systems (feedlot x pasture). However, the amount of the concentrate used was 82% of the diet.…”
Section: Resultsmentioning
confidence: 99%